MODERN EQUIPMENT FOR REFINING AND CASTING OF STEEL AND ALLOYS IN FOUNDRY PRODUCTION - V. I. Zolotukhin; A. G. Golovko; E. I. Gordeev; D. A. Provotorov (Литьë и металлургия, 2018)
The article deals with the issues of complex technology and equipment for refining and casting steel and alloys in the foundry industry. Solutions are given that make it possible to guarantee a reduction in nonmetallic inclusions in the melt, as well as to solve a number of other related problems of foundry production, such as the introduction of a bottom blowing melt system with an inert gas; the introduction of protection of the metal stream from secondary oxidation; lining the arch of an electric arc furnace, etc. Various types of products and equipment produced by NPP Vulkan-TM are shown: blowing bottom plugs and assemblies, metering nozzles, gas-dynamic protection of the metal stream from secondary oxidation, two-arm wire-feeding machine mod. TAP 2–1 with unwinding device.Advantages of the equipment for steel casting and extra-furnace steel processing are described.